Diet and trophic niche of the endangered fish Garra ghorensis in three Jordanian populations. Issue 3 (23rd April 2015) - Hamidan, Nashat; Jackson, Michelle C.; Britton, J.R.
Abstract: Garra ghorensis is a small riverine cyprinid fish endemic to the southern Dead Sea that is endangered through habitat loss and invasive species. Here, their diet and trophic niche were assessed in three Jordanian populations: an allopatric population, a population sympatric with native Capoeta damascina and a population sympatric with invasive Oreochromis aureus . Stomach content analyses of samples collected between February 2011 and January 2012 revealed that detritus and algae were prominent food items in their diets, with low dietary contributions of animal material. The most frequent and abundant macro‐invertebrates in intestines were Odonata nymphs and gastropod species. The calculation of trophic niche size from the stomach content data revealed that the niche of G. ghorensis (0.10) was generally smaller than sympatric C. damascina (0.24), with an overlap of 72%, whereas they had a larger trophic niche than sympatric O. aureus (0.20–0.13), with a niche overlap of 54%. These outputs were generally supported by stable isotope analyses of δ 13 C and δ 15 N completed on samples collected at the end of the 2011 growth season, although these indicated a greater contribution of animal material to assimilated diet. They also indicated that the trophic niche breadth [as standard ellipse area (SEA)] of C. damascina (4.18‰ 2 ) was higher than G. ghorensis (2.48‰ 2 ) and overlapped by 26%. For G. ghorensis, their SEA was slightly larger than O. aureus (4.33–4.00‰ 2 ), with an overlap of 27%. Although both methods indicated some sharing of food resources between sympatric fishes, there was no evidence suggesting detrimental outcomes for G. ghorensis and thus was not considered as a constraint on the status of their populations.